Incidence, pathology and involvement of Nasitrema species in odontocete strandings in the Canary Islands - Degollada, Eduard; André, Michel; Arbelo Hernández, Manuel Antonio; Fernández Rodríguez, Antonio Jesús (Veterinary Record, 2002)
82 81 1,221 Q1 SCIE